PERAN HUKUM DALAM MENANGGULANGI TINDAK PIDANA PEMALSUAN DOKUMEN DI INDONESIA (The Role of Law in Combating Document Forgery Crimes in Indonesia) - Alfatih, Nanda Karunia; Raharjo, Eko; Amrullah, Rinaldy (RIO LAW JURNAL, 2025)
Document forgery is a serious issue that affects various sectors of life in Indonesia, including social, economic, and political systems. Document forgery involves the act of creating or altering documents to make them appear valid and genuine with the intent to deceive or gain unlawful benefits. This practice has become more complex with the advancement of information technology, enabling the forgery of electronic documents that are difficult to detect. This study examines the role of law in addressing document forgery in Indonesia, the challenges faced in law enforcement, and solutions that can be implemented to enhance the effectiveness of law enforcement. This research uses a qualitative approach by reviewing various legal regulations, case studies, and previous research to understand the root causes of document forgery. The findings show that although regulations are in place to address document forgery in the Criminal Code (KUHP) and the new Law No. 1 of 2023, the biggest challenge in law enforcement is the difficulty in proving forgery, particularly in relation to electronic documents. Additionally, the lack of capacity among law enforcement in digital forensic technology and the general public's lack of awareness are significant barriers. Therefore, improving the capacity of law enforcement, updating regulations, and raising public awareness are necessary to make law enforcement against document forgery more effective and efficient. This study provides recommendations for strengthening Indonesia's legal system in dealing with document forgery in a more comprehensive manner.Keywords: Document Forgery, Criminal Law, Electronic Documents, Law Enforcement, Digital Forensics